Pelatihan Pembuatan Bahan Ajar Peduli Lingkungan Berbasis Kearifan Lokal Pada Guru Sekolah Dasar - Erlisnawati; Marhadi, Hendri; Hermita, Neni; Alpusari, Mahmud; Syahrilfuddin, Syahrilfuddin (Journal of Community Engagement Research for Sustainability, 2023)
Abstract Teaching materials are components that have an important role in carrying out learning process activities. Teaching materials used by teachers will support the mastery of competencies achieved through learning activities. These competencies are not only related to knowledge but also about attitudes and skills. One of the attitudes as a competency possessed by students is caring for the environment. The inculcation of an attitude of caring for the environment through the learning process must be supported by the use of relevant teaching materials, one of which is teaching materials for environmental care based on local wisdom. This service program aims to improve the ability of teachers to make teaching materials based on local wisdom. This activity was carried out using a classical approach to shared perceptions about teaching materials for environmental care based on local wisdom through zoom meetings and a practical approach to making teaching materials accompanied by a Service Team by visiting schools where teachers are the target community. This activity was carried out in August – October 2022. Based on the results of the training carried out, it can be concluded that the service activities carried out ran smoothly and produced environmental care teaching materials based on Silek Nekar Tuah local wisdom. Keywords: Teaching Materials; Environmental Care, Local Wisdom